Pengembangan WEBGIS Untuk Optimalisasi Link and Match SMK Agribisnis dan Industri Pangan di Jawa Barat - Khoerunnisa, Indah; Rizalita, Rafiqa; Nalendro, Putut Aji; Firdian, Fadil; Surawan, Ghea Chandra (Universitas Lampung, 2024)
The misalignment between vocational education and industry needs remains a major challenge in Indonesia’s vocational education system. Data shows high unemployment rates among vocational high school (SMK) graduates, reflecting the gap between their competencies and industry needs. This study aims to develop WebGIS, a web-based geographic information system, to optimize the relationship and fit between SMK Agribusiness Agricultural Product Processing (APHP) and the food industry in West Java. The WebGIS was developed using the waterfall model, comprising four stages: needs analysis, system design, implementation, and testing. The mapping integrates data from 47 SMKs and 105 food industries in West Java. Usability testing using the System Usability Scale (SUS) showed an acceptance rate categorized as